Project-Based Learning Implementation in Improving Students’ Skills at SMK Negeri 1 Tangerang - Lina Sukanti; Sutarman Sutarman; Imraan Mohd (The International Journal of Education Management and Sociology, 2025)
This study aims to examine the implementation of Project-Based Learning (PjBL) in improving students’ skills at SMK Negeri 1 Tangerang. This approach is considered relevant for vocational education as it seeks to produce graduates with strong practical skills, problem-solving abilities, and high workplace readiness. The study employs a qualitative descriptive method through observations, interviews, and document analysis. The findings indicate that the application of PjBL significantly fosters active student participation, enhances creativity, and strengthens collaboration in completing project-based tasks. Furthermore, PjBL supports students in mastering vocational competencies more effectively, as they are directly involved in the planning, execution, and evaluation of the project. However, several challenges were identified, including limited facilities, relatively short instructional time, and variations in students’ abilities that influence the overall effectiveness of the learning process. Overall, the implementation of PjBL proves to be an effective instructional strategy in enhancing students’ skills at SMK Negeri 1 Tangerang.